2019
DOI: 10.5811/westjem.2019.7.42671
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Post-Traumatic Stress Disorder in Emergency Physicians in the United States

Abstract: There is increasing concern about the effects of occupational stressors on the wellness of healthcare providers. Given high patient acuity, circadian rhythm disruption, and other workplace stressors, emergency physicians (EP) would be predicted to have high rates of occupational stress. We conducted this study to assess the prevalence of post-traumatic stress disorder (PTSD) in attending EPs practicing in the United States. Methods: A link to an electronic questionnaire was distributed through the emergency me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…However, students interested in EM may not be appropriately acknowledging the significance of the chronic and consistent stress that EM physicians are regularly exposed to and thus do not recognize that the potential stress and hardship of EM cannot be overcome by simply having more time off as a trade‐off. In fact, it has been suggested those working in EM could be suffering from posttraumatic stress disorder directly related to their acute and chronic exposure to their “front‐line” patient care responsibilities 10,11,12,13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, students interested in EM may not be appropriately acknowledging the significance of the chronic and consistent stress that EM physicians are regularly exposed to and thus do not recognize that the potential stress and hardship of EM cannot be overcome by simply having more time off as a trade‐off. In fact, it has been suggested those working in EM could be suffering from posttraumatic stress disorder directly related to their acute and chronic exposure to their “front‐line” patient care responsibilities 10,11,12,13…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been suggested those working in EM could be suffering from posttraumatic stress disorder directly related to their acute and chronic exposure to their "front-line" patient care responsibilities. [10][11][12][13] Medical school career planning activities may be one means by which these observations and findings could be discussed. Ensuring that messaging from career advisors, mentors, and others include a consideration about the effects of stress that is distinguishing of EM as a field would be helpful in improving this as a priority among trainees.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the incidence of high levels of stress in healthcare workers during an epidemic or pandemic range from 18.1% to 80.1%. 6 Sources of stress may include increased workload, fears of contagion for themselves and their families, working with new and frequently changing protocols and personal protective equipment (PPE), caring for critically ill patients, and caring for colleagues who have also fallen ill. 7 Several studies have identified high incidences of anxiety, depression, and stress among healthcare workers during this pandemic. 8,9 Among the findings in a 2020 study during the height of the coronavirus disease 2019 (COVID-19) pandemic in New York City were that more than half had high levels of acute stress, nearly half had depression symptoms, one third had anxiety, and most had insomnia and loneliness.…”
Section: Importancementioning
confidence: 99%
“…Healthcare Workers (HCWs) in emergency care settings are particularly at risk for PTSD because of the highly stressful work-related situations they are exposed to, that include: management of critical medical situations, caring for severely traumatized people, frequent witnessing of death and trauma, operating in crowded settings, interrupted circadian rhythms due to shift work) ( Figley, 1995 ; Crabbe et al., 2004 ; Cieslak et al., 2014 ; Berger et al., 2012 ; Hegg-Deloye et al., 2013 ; Garbern et al., 2016 ). PTSD rates have been reported to range from 10 to about 20% ( Grevin, 1996 ; Clohessy and Ehlers, 1999 ; Robertson and Perry, 2010 ; DeLucia et al., 2019 ), with even higher PTSD rates (8% to 30%) among Intensive Care Unit (ICU) staff, ( Mealer et al., 2009 ; Karanikola et al., 2015 ; Machado et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%